2014
DOI: 10.1177/1363459314539774
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strategies of personal resilience on depression recovery in an Australian cohort: A mixed methods study

Abstract: Strategies of personal resilience enable successful adaptation in adversity. Among patients experiencing depression symptoms, we explored which personal resilience strategies they find most helpful and tested the hypothesis that use of these strategies improves depression recovery. We used interview and survey data from the Diagnosis, Management and Outcomes of Depression in Primary Care 2005 cohort of patients experiencing depression symptoms in Victoria, Australia. A total of 564 participants answered a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Dowrick, Kokanovic, Hegarty, Griffiths, and Gunn () found in a qualitative study that interpersonal support was a consolidated resilience strategy for people with symptoms of depression. In contrast, Griffiths et al () reported that drawing on relationships was not longitudinally associated with improvement in patients with depressive symptoms, and Rea et al () reported that social support improved outcomes of relapse and recurrence in BD, showing fewer mood disorder relapses and fewer probabilities of being rehospitalized over the 2‐year study period. Although the longitudinal path in the present study between the resilience domain of interpersonal support at T1 and personal recovery at the 6‐month follow‐up represented a small effect size, it is still relevant, as the path analysis displays the unique predictive role of resilience factors in personal recovery.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Dowrick, Kokanovic, Hegarty, Griffiths, and Gunn () found in a qualitative study that interpersonal support was a consolidated resilience strategy for people with symptoms of depression. In contrast, Griffiths et al () reported that drawing on relationships was not longitudinally associated with improvement in patients with depressive symptoms, and Rea et al () reported that social support improved outcomes of relapse and recurrence in BD, showing fewer mood disorder relapses and fewer probabilities of being rehospitalized over the 2‐year study period. Although the longitudinal path in the present study between the resilience domain of interpersonal support at T1 and personal recovery at the 6‐month follow‐up represented a small effect size, it is still relevant, as the path analysis displays the unique predictive role of resilience factors in personal recovery.…”
Section: Discussionmentioning
confidence: 95%
“…Dowrick, Kokanovic, Hegarty, Griffiths, and Gunn (2008) found in a qualitative study that interpersonal support was a consolidated resilience strategy for people with symptoms of depression. In contrast, Griffiths et al (2014) reported that drawing on relationships was not longitudinally associated with improvement in and having health beliefs and limits), which have been found to be associated with lower rates of relapses and to improve adherence and wellness in BD (Berk et al, 2004). Previous studies (Berk et al, 2004;Rea et al, 2003) have reported that some strategies-which are similar to the resilience domains of interpersonal support, self-care, and self-confidence-are longitudinally associated with improvement of mental health in BD, but they did not assess their longitudinal associations with personal recovery.…”
Section: Longitudinal Associations Between Resilience and Adjustmenmentioning
confidence: 90%
See 2 more Smart Citations
“…The value of focusing on strategies such as time for self is that they are relatively low intensity and low cost . However, it is important to acknowledge that getting time for self requires the ongoing and frequent support of others—partners, family, friends, neighbors, or paid childcare services.…”
Section: Discussionmentioning
confidence: 99%